Do university entrepreneurship programs promote entrepreneurship? - Eesley, Charles E.; Lee, Yong Suk (Strategic Management Journal, 2021)
Abstract Research summary We examine how university entrepreneurship programs affect entrepreneurial activity using a unique entrepreneurship‐focused survey of Stanford alumni. OLS regressions find a positive relationship between program participation and entrepreneurship activities. However, endogeneity hinders causal interpretation. We utilize the fact that the entrepreneurship programs were implemented at the school level. Using the introduction of each school's program as an instrument for program participation, we find that the Business School program has a negative to zero impact on entrepreneurship rates. Participation in the Engineering School program has no impact on entrepreneurship rates. However, the Business School initiative decreases startup failure and increases firm revenue. University entrepreneurship programs may not increase entrepreneurship rates, but help students better identify their potential as entrepreneurs and improve the quality of entrepreneurship. Managerial summary Recently, many universities have developed programs to promote entrepreneurship. However, relatively little is known about the impacts of such university initiatives. In this article, we examine the two major initiatives that were established in the mid‐1990s—the Stanford Center for Entrepreneurial Studies at the Business School and the Stanford Technology Ventures Program at the Engineering School. We find that the Business School program had a negative to zero impact on entrepreneurship rates and participation in the Engineering School program had no impact on entrepreneurship rates. However, the Business School initiative decreased startup failure and increased firm revenue. University entrepreneurship programs may not increase entrepreneurship rates, but help students better identify their potential as entrepreneurs and improve the startup performance.